Role of miRNAs in glucose metabolism of mouse cumulus cells - Ma, Rui-Jie; Zhang, Min; Wu, Jia-Shun; Wang, Zhi-Peng; Wang, Guo-Liang; He, Nan; Luo, Ming-Jiu; Tan, Jing-He (Biology of reproduction, 2024)
It is known that the oocyte has a limited capacity to acquire and metabolize glucose, and it must rely on cumulus cells (CCs) to take up glucose and produce pyruvate for use to produce ATP through oxidative phosphorylation. We therefore propose that miRNAs might regulate glucose metabolism (GM) in CCs and might be used as markers for oocyte quality assessment. Here, mouse CC models with impaired glycolysis or pentose phosphate pathway (PPP) were established, and miRNAs targeting the key enzymes in glycolysis/PPP were predicted using the miRNA target prediction databases. Expression of the predicted miRNAs was compared between CCs with normal and impaired glycolysis/PPP to identify candidate miRNAs. Function of the candidate miRNAs was validated by transfecting CCs or cumulus-oocyte-complexes (COCs) with miRNA inhibitors and observing effects on glucose metabolites of CCs and on competence of oocytes. The results validated that miR-23b-3p, let-7b-5p, 34b-5p and 145a-5p inhibited glycolysis, and miR-24-3p, 3078-3p,183-5p and 7001-5p inhibited PPP of CCs. Our observation using a more physiologically relevant model (intact cultured COCs) further validated the four glycolysis-targeting miRNAs we identified. Furthermore, miR-let-7b-5p, 34b-5p and 145a-5p may also inhibit PPP, as they decreased the production of glucose-6-phosphate. In conclusion, miRNAs play critical roles in GM of CCs and may be used as markers for oocyte quality assessment. Summary Sentence We identified and validated eight new miRNAs that inhibit glycolysis and/or pentose phosphate pathways in cumulus cells (CCs) suggesting that miRNAs play critical roles in glucose metabolism of CCs and may be used for oocyte quality markers. Graphical Abstract